1997
DOI: 10.1021/bi962789p
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Cross-Linking of the Human Immunodeficiency Virus Type 1 Tat Protein to Synthetic Models of the RNA Recognition Sequence TAR Containing Site-Specific Trisubstituted Pyrophosphate Analogues

Abstract: A chemical ligation procedure has been developed for the synthesis of oligoribonucleotides carrying a trisubstituted pyrophosphate (tsp) linkage in place of a single phosphodiester. Good yields of tsp were obtained when a single 2'-deoxynucleoside 5' to the tsp was used in the ligation reaction. A tsp linkage was found to be reasonably stable to hydrolysis but cleaved by treatment with ethylenediamine or lysine to give phosphoamidate adducts. A model human immunodeficiency virus type 1 (HIV-1) TAR RNA duplex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Importantly, the covalent bond between a DNA phosphate group and a histidine is cleaved by treatment with N-MeIm, whereas the bond between DNA phosphate and other nucleophilic amino acids is stable under these conditions (25). We also have established that DNA duplexes bearing SPI groups can cross-link with nucleophilic amino acids from DNA-binding enzymes situated within the DNA interface under near-physiological conditions (16,(23)(24)(25)(26). More recently, it has been shown that Fpg can cover six nucleotides on the damaged strand and also make contacts with the complementary strand (27).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Importantly, the covalent bond between a DNA phosphate group and a histidine is cleaved by treatment with N-MeIm, whereas the bond between DNA phosphate and other nucleophilic amino acids is stable under these conditions (25). We also have established that DNA duplexes bearing SPI groups can cross-link with nucleophilic amino acids from DNA-binding enzymes situated within the DNA interface under near-physiological conditions (16,(23)(24)(25)(26). More recently, it has been shown that Fpg can cover six nucleotides on the damaged strand and also make contacts with the complementary strand (27).…”
Section: Resultsmentioning
confidence: 95%
“…1A) were synthesized by chemical ligation (13). We established previously that nucleic acid fragments containing an SPI group are easily and quantitatively cleaved by primary and secondary amines, including nucleophilic amino acids (16,23). The reaction mechanism involves nucleophilic attack at the disubstituted phosphorous atom of the SPI group and elimination of an oligonucleotide remnant that contains the 3Ј-O-ethylphosphate derived from the modified phosphate of the pyrophosphate linkage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical modi¢cations of de¢ned positions in a DNA probe have been previously shown to allow crosslinking of the corresponding DNA binding region of the transcription factor. Sets of DNA or RNA duplexes with chemically active internucleotide linkages were successfully used for a⁄nity modi¢cation and probing the nucleic acid binding regions of restriction^modi¢cation enzymes [10], of RNA recognizing TAT peptide [11] and of transcription factors [12]. Recently, a new class of reactive double-stranded (ds) DNA derivatives which can crosslink with proteins recognizing speci¢c nucleic acid sequences was investigated [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently a new class of preactive double‐stranded DNA and RNA derivatives which are able to crosslink with proteins recognizing specific nucleic acid sequences was proposed in our laboratory [1, 2]. Trisubstituted pyrophosphate [1–6]or acylphosphate [7]linkages incorporated at predetermined positions in double‐stranded nucleic acids permit crosslinking with nucleophilic amino acids (Lys and His) right at the protein active site or binding region (at zero distance) without any influence from the outside. Sets of DNA or RNA duplexes with chemically active internucleotide linkages were successfully used for affinity modification and probing the nucleic acid binding regions of restriction‐modification enzymes [2, 8], RNA recognizing TAT peptide [4]and transcription factors NF‐κB [3, 5, 9]and HNF1 [6].…”
Section: Introductionmentioning
confidence: 99%